Investigation of negative capacity converters for broad-band matching of electrically-small antennas - D. V. Belenko; A. A. Golovkov; E. I. Mozhaeva (Известия высших учебных заведений России: Радиоэлектроника)
The analysis of the characteristics and stability of negative impedance converter for com.pensation impedance capacitive com.ponent of electrically small whip antenna to increase its gain. The obtained theoretical results are confirmed by experimental research.